A review on the physiological and therapeutic effects of Śankhaprakṣhālana kriyā (yogic bowel cleansing) - Jaydeep Negi; Abhishek Kumar Bhardwaj; Sachin Kumar (Wolters Kluwer Medknow Publications, 2022)
Śankhaprakṣhālana (SP) kriyā is an integral component of ṣaṭkarmas (the six cleansing practices of Haṭha Yoga). It involves drinking lukewarm salt water in combination with dynamic yoga āsanas which leads to the cleansing of the entire alimentary canal. The objectives of this study are to systematically elucidate the practice of SP kriyā and to collate and review studies that highlight its immediate and long-term physiological and therapeutic effects. Keywords such as "shankha prakshalana, laghu shankha prakshalana, varisara dhauti, and yogic colon cleansing" were used for search in multiple research databases. A total of 12 studies with SP kriyā as the main intervention were included in this review. Eight studies have reported the immediate effects of SP. The practice of SP immediately benefits in primary hypertension and chronic low back pain. Clinical studies support its effective use as a colonoscopy preparation. There is no risk of electrolyte imbalance, blood pressure, and pulse rate changes in healthy individuals after SP. The technique of drinking saline along with dynamic āsanas plays a significant role in faster bowel cleansing. Other four studies have reported the long-term (1-2 months) effects of SP with variations in the frequency and duration of practice. SP is found beneficial in managing digestive issues such as constipation, migraine-associated abdominal discomfort, and irritable bowel syndrome. It is also an effective weight management practice for obese. Hence, the practice offers diverse health benefits. Further clinical trials are required to support the findings in clinical populations and to determine the effective frequency and total duration of the practice in the long term.